Pediatric mucinous neoplasm of the appendix presenting as a mucocele: A case report and review of the literature - Barrie S. Rich; Sudarshana Roychoudhury; Alex K. Williamson; Richard D. Glick (Elsevier, 2017)
Mucocele of the appendix is a rare entity in pediatrics, with few case reports in the literature. We present a case of a 17-year-old male with right lower quadrant pain who was found to have an appendiceal mucocele while being evaluated for appendicitis. Laparoscopic-assisted resection was performed, with pathology confirming a low-grade mucinous neoplasm of the appendix, a tumor scarcely described in the pediatric population. He underwent complete resection with negative margins, rendering him cured without the need for any further resection or treatment. We review the literature on this topic.